2010
DOI: 10.1371/journal.pone.0009108
|View full text |Cite
|
Sign up to set email alerts
|

The Manual Habituation and Discrimination of Shapes in Preterm Human Infants from 33 to 34+6 Post-Conceptional Age

Abstract: BackgroundGrasping at birth is well-known as a reflex in response to a stimulation of the palm of the hand. Recent studies revealed that this grasping was not only a pure reflex because human newborns are able to detect and to remember differences in shape features. The manual perception of shapes has not been investigated in preterm human infants. The aim of the present study was to investigate manual perception by preterm infants.Methodology/Principal FindingsWe used a habituation/reaction to novelty procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
3
29
2
5
Order By: Relevance
“…First, the results confirmed the presence of haptic manual habituation for each hand and for each shape in preterm infants between 33 and 34 + 6 GW. However, contrary to our previous study with 24 infants and an identical habituation procedure (Lejeune et al, 2010), a main effect of hand was observed for two parameters of habituation: Preterm infants held objects with the right hand longer than with the left hand during the first two and the last two trials of habituation. Even if few similar asymmetries have previously been found, they suggest in some samples stronger grasping with the right hand (Caplan & Kinsbourne, 1976;Petrie & Peters, 1980).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…First, the results confirmed the presence of haptic manual habituation for each hand and for each shape in preterm infants between 33 and 34 + 6 GW. However, contrary to our previous study with 24 infants and an identical habituation procedure (Lejeune et al, 2010), a main effect of hand was observed for two parameters of habituation: Preterm infants held objects with the right hand longer than with the left hand during the first two and the last two trials of habituation. Even if few similar asymmetries have previously been found, they suggest in some samples stronger grasping with the right hand (Caplan & Kinsbourne, 1976;Petrie & Peters, 1980).…”
Section: Discussioncontrasting
confidence: 99%
“…Using a classic habituation-reaction to novelty procedure (without visual control), Streri et al (2000) showed that fullterm newborns, tested at 2 days of age, were able to memorize tactile information about specific shape features (prism or cylinder) and detect differences between these two shapes with either the right or left hand. Similar abilities have been found in preterm infants from 33 to 34 + 6 GW (Lejeune et al, 2010) and were not influenced by hand, shape and preterms' medical history.…”
supporting
confidence: 79%
“…The previous study published in February 2010 by Lejeune and her collaborators 9 showed that from 33 to 34+6 GW, preterm infants were capable of manual habituation to, and discrimination of shapes. The current study, carried out in the same experimental conditions, revealed that the more immature preterm infants, from 28 GW, were able to remember through touch the specific features that differentiate prism and cylinder shapes, discriminate between them, and then recognize them after interference (presentation of a novel object).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Lejeune and her collaborators 9 investigated the ability of preterm infants' hands to perceive and discriminate between various shapes. Twenty-four preterm infants of a postconceptional age (PCA) of 33 to 34+6 weeks were tested; the results showed that they were able to detect by touch the specific features that differentiate prism and cylinder shapes, and remember them.…”
Section: Methodsmentioning
confidence: 99%
“…В позднем восстановительном периоде регулярные заня-тия с ладонями и пальцами ускоряют появление слухо-вого и зрительного сосредоточения, активных движений рук, «пинцетообразного» захвата и противопоставления большого пальца, а также стимулируют гуление с более разнообразными вокализациями [25,27,29].…”
Section: традиционная основа физической абилитации -методы массажа и unclassified